Can We Stop and Listen Now? - Belchior-Rocha, H.; Mauritti, R (Beyond COVID-19, 2022)
The objective of this chapter is to present, in a systematic way, the most recent data that shows the general consequences of the situation experienced in our country (Portugal), since the beginning of the Contingency Plans — COVID-19, focusing on the impact felt in higher education institutions and in the analysis of requirements and challenges to be faced by higher education and its institutions. Thus, in order to find effective ways of acting on the effects of this crisis/challenge, in a proactive way, relearning a critical attitude to understand the constant societies crises, with which we are currently struggling, our proposal is to prepare students to face unexpected and increasingly frequent situations. Although in addition to the specific knowledge of each area, associate transversal, transferable and soft skills, to articulate with interdisciplinary teams, promoting their adaptation and resilience, inner-self-knowledge, empathy, social responsibility awareness and recover the fundamental value of BEING.